Nano-delivery platform with strong protection and efficient delivery: preparation of self-assembled RNA pesticide with dual RNAi targets against Apolygus lucorum - Heng Qiao; Qinhong Jiang; Jing Zhao; Liubin Xiao; Keyan Zhu-Salzman; Dejin Xu; Guangchun Xu; Jie Shen; Aiguo Gu; Dejun Hao; Shuo Yan; Yongan Tan (Journal of Nanobiotechnology)
Abstract Background RNA pesticide is regarded as the “third revolution in the history of pesticides”. However, the double-stranded RNA (dsRNA) is easily degraded in the environment, and its delivery efficiency is not sufficient for pest management. This study aimed to construct a star polycation (SPc)-based delivery platform with strong protection and efficient delivery to develop a self-assembled RNA pesticide with dual RNA interference (RNAi) targets. Results The nanocarrier SPc was applied to assemble with dsRNA via electrostatic interaction, hydrogen bond and Van der Waals force, and the self-complexation with SPc formed nanoscale dsRNA/SPc complex. The SPc could protect the dsRNA from the degradation by midgut fluid or RNase A, thus significantly increasing the stability of dsRNA under various environmental conditions. Meanwhile, the SPc was able to improve the translocation of dsRNA across insect cuticle, and increase its plant uptake. Then, dsECR-A and dsTre-1 fragments were individually screened, and the dsECR-A and dsTre-1 fragments with good control effects were co-expressed in pET28-BL21 (DE3) RNase III − system to prepare the dsECR-A + Tre-1/SPc complex. Both topical application and spraying of dsECR-A + Tre-1/SPc complex could effectively control a piercing-sucking agricultural pest Apolygus lucorum. The SPc-loaded dsECR-A + Tre-1 could up-regulate endocytosis-related genes and down-regulate cuticle biosynthesis-related genes, which primarily inhibited insect growth and development. Conclusions Our study comprehensively demonstrated the advantages of SPc-based dsRNA delivery platform, and developed a self-assembled RNA pesticide with dual RNAi targets, which provided a reference for the design of novel RNA pesticides. Graphical abstract